Knowledge management readiness and knowledge management planning in craft industry (case study: woodka) - Handayani, Melia; Hendarman, Achmad Fajar (The Indonesian Journal of Business Administration, 2019)
Abstract. Based on data from Bekraf Indonesia . there are three most significant sub-sectors of industry, namely fashion, culinary, and craft. Woodka is a company included in the craft industrycategory in Indonesia. Woodka's production consists of jam with wood-based materials made by local craftsmen. To still be able to overcome the increasingly rapid competition in the craft industry, Woodka must improve the performance of its employees so that they can continue to innovate the company. Before innovating further, the company must know Knowledge Management Readiness in the company. Knowledge management readiness will measure the level of preparedness of companies in Woodka to manage their knowledge and apply it to the company. Based on the questionnaire, the most significant given is in the variable process. In the process of a variable gap between current conditions and expectations is 1.1. That is, with the current perception score of 3.4 and expectations 4.5. The most significant amount compared to other variables. For the perception score entered into the refinement of the category. The second considerable gap after the process is system management within the Woodka company. The way Woodka gives rewards to employees is also an essential factor in improving employee competency. In this study, the gap between perception and expectation is 1.1.Perception score 3.4 From the most significant gap obtained, we know about KM Woodka at this time, namely, process factors and system management factors that must be corrected, so suggestions from Woodka researchers make their experience for KM projects for their employees. A company must establish a way to build good communication compilation among companies in using the SECI Model with joint socialization, externalization, combination, and internalization.Keywords: Knowledge Management Readiness, SECI Model, Craft Industry